2004
DOI: 10.1016/j.ceca.2004.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ oscillations mediated by exogenous GTP in Paramecium cells: assessment of possible Ca2+ sources

Abstract: We applied exogenous guanosine trisphosphate, GTP, to Paramecium tetraurelia cells injected with Fura Red for analysing changes of free intracellular Ca 2+ concentrations, [Ca 2+ ] i , during periodic back-/forward swimming thus induced. Strain ginA (non-responsive to GTP) shows no Ca 2+ signal upon GTP application. In strain nd6 (normal Ca 2+ signalling) an oscillating [Ca 2+ ] i response with a prominent first peak occurs upon GTP stimulation, but none after mock-stimulation or after 15 min adaptation to G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 83 publications
0
17
0
Order By: Relevance
“…When Paramecium tetraurelia cells are exposed to extracellular GTP, ≥10 µM, this causes periodic forward and backward swimming (different from ciliary reversal) in ∼8 s intervals; this is accompanied by oscillating membrane depolarisations (Clark, Hennessey & Nelson, ) and by oscillating intracellular Ca 2+ signals (Sehring & Plattner, ) that are consistent with oscillating Ca 2+ currents (Mimikakis, Nelson & Preston, ). This effect is specific to GTP and cannot be induced by any other nucleotide triphosphate in any comparable concentration.…”
Section: Surface Receptors For Intracellular Signallingmentioning
confidence: 99%
See 2 more Smart Citations
“…When Paramecium tetraurelia cells are exposed to extracellular GTP, ≥10 µM, this causes periodic forward and backward swimming (different from ciliary reversal) in ∼8 s intervals; this is accompanied by oscillating membrane depolarisations (Clark, Hennessey & Nelson, ) and by oscillating intracellular Ca 2+ signals (Sehring & Plattner, ) that are consistent with oscillating Ca 2+ currents (Mimikakis, Nelson & Preston, ). This effect is specific to GTP and cannot be induced by any other nucleotide triphosphate in any comparable concentration.…”
Section: Surface Receptors For Intracellular Signallingmentioning
confidence: 99%
“…This response to nucleotide triphosphates is unexpected insofar as there are no purinergic receptors known from ciliates (Burnstock & Verkhratsky, ; Coddou et al, ; Verkhratsky & Burnstock, ), in contrast to Dictyostelium discoideum (Fountain et al, ). In Paramecium tetraurelia GTP‐induced signalling involves release of Ca 2+ from unidentified internal stores (Wassenberg, Clark & Nelson, ), but a stronger first Ca 2+ peak depends on [Ca 2+ ] o (Sehring & Plattner, ). The biological significance of these Ca 2+ oscillations and of the repetitive back/forward movement is not quite clear, but it was suggested that the GTP‐induced behaviour counteracts dispersal of the cells (Sehring & Plattner, ).…”
Section: Surface Receptors For Intracellular Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…). This is paralleled by periodic changes in [Ca 2+ ] i signals (Sehring and Plattner ). Based on inhibitor studies, the source of Ca 2+ underlying this signal was attributed to alveolar sacs (Wassenberg et al.…”
Section: Focusing Still More On Details Specific For Parameciummentioning
confidence: 93%
“…Considering that the pharmacology used is aberrant in Paramecium (Plattner et al. ) one may envisage some other stores which are important particularly for the first peak seen with a fluorochrome after GTP stimulation (Sehring and Plattner ). Which one of the many organelles endowed with CRCs (see below) this would be has not been determined as yet.…”
Section: Focusing Still More On Details Specific For Parameciummentioning
confidence: 99%